2013
DOI: 10.1186/1475-2840-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin A1c even within non-diabetic level is a predictor of cardiovascular disease in a general Japanese population: the Hisayama Study

Abstract: BackgroundThere is little information about predictive ability of haemoglobin A1c (HbA1c) for cardiovascular disease (CVD) in Asians. To investigate the discriminatory ability of HbA1c to identify subjects who are at greater risk of developing CVD in a prospective study of a defined community-dwelling Japanese population.MethodsA total of 2,851 subjects aged 40–79 years were stratified into five groups (HbA1c levels with ≤ 5.0, 5.1–5.4, 5.5–6.4, and ≥ 6.5% and a group with antidiabetic medication) and followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…Therefore, a score is necessary to improve diagnostic precision, particularly because the prevalence of non-obstructive CAD on angiography may be greater than 50% in some populations [9]. The results from a community-dwelling Japanese population suggest that HbA1c levels are an independent risk factor for CAD [13]. Another study indicated that HbA1c was an independent risk factor for the presence of severe CAD (Beta = 0.374, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a score is necessary to improve diagnostic precision, particularly because the prevalence of non-obstructive CAD on angiography may be greater than 50% in some populations [9]. The results from a community-dwelling Japanese population suggest that HbA1c levels are an independent risk factor for CAD [13]. Another study indicated that HbA1c was an independent risk factor for the presence of severe CAD (Beta = 0.374, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin A 1c (HbA 1c ) is widely used as a marker of average blood glucose concentrations over the preceding 2 to 3 months and it has advantages over glucose tests [7] . Some evidence indicates that high HbA 1c levels prior to surgery are strongly associated with the severity of adverse events after CABG [8] .…”
Section: Introductionmentioning
confidence: 99%
“…HbA1c is also linearly related to the risk of CVD and diabetes in non-diabetic individuals [61,62]. The mortality curve associated with HbA1c levels is U-shaped, with the lowest death rates for values between 5.0 and 5.5% [63].…”
Section: Hba1cmentioning
confidence: 99%